Forensic application of foot dimensions in ethnic differentiation among Ghanaians - Adjei-Antwi, Collins; Nketsiah, James; Darkoa Darko, Nancy; Kusi Appiah, Atta; Joshua, Tetteh; Abaidoo, Chrissie Stansie (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Foot dimensions are known parameters for height estimation and personal identification in most developed countries but there appears to be dearth of information about their utilization in developing countries. Therefore, the present study sought to provide ethnic-specific baseline data on foot dimensions and bring to light the differences that exist between some ethnic groups in Ghana. Methods: One hundred and ninety-three undergraduate students consisting of Ashantis, Fantes and Ewes were recruited.  Plantar surfaces were scanned and foot dimensions were taken. Results: The left 1st, right 2nd and 3rd toe-pternion lengths and the right breadth at ball were the only dimensions that exhibited differences between the Ashanti and Fante ethnic groups. However, differences were recorded between the Ashanti and Ewe feet for all the measurements taken. Also, with the exception of the right 5th toe-pternion length, all the dimensions exhibited differences. Conclusions: Inter-ethnic differences exist for the dimensions of the foot between the ethnic groups that were involved in the present study. The present study has provided ethnic specific baseline data on foot dimensions for identification purposes.